2016
DOI: 10.1080/21622965.2016.1167500
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory and Neurofeedback

Abstract: Impairments in working memory are typically associated with impairments in other cognitive faculties such as attentional processes and short-term memory. This paper briefly introduces neurofeedback as a treatment modality in general, and, more specifically, we review several of the current modalities successfully used in neurofeedback (NF) for the treatment of working memory deficits. Two case studies are presented to illustrate how neurofeedback is applied in treatment. The development of Low Resolution Elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Cicerone et al (2011) concluded that attention seems to train better than other domains of cognition. For treatment of children with attention deficit/hyperactivity disorder (ADHD), NF has been shown to be a better intervention than traditional attention (Hurt et al, 2014; Steiner et al, 2014) or WM training (YuLeung To et al, 2016). Notice though, evidence from meta-analyses of randomized controlled trials fails to support NF as an effective treatment for ADHD in children and adolescents.…”
Section: Neurofeedback (Nf)mentioning
confidence: 99%
“…Cicerone et al (2011) concluded that attention seems to train better than other domains of cognition. For treatment of children with attention deficit/hyperactivity disorder (ADHD), NF has been shown to be a better intervention than traditional attention (Hurt et al, 2014; Steiner et al, 2014) or WM training (YuLeung To et al, 2016). Notice though, evidence from meta-analyses of randomized controlled trials fails to support NF as an effective treatment for ADHD in children and adolescents.…”
Section: Neurofeedback (Nf)mentioning
confidence: 99%
“…Of the nine that were excluded, five included only nonclinical subjects and were considered proof of concept studies and did not test clinical efficacy. The remaining four were either case studies (YuLeung To et al 2016 ), case series (Koberda et al 2012 ), or not a study at all but a discussion of related topics (Cannon 2012 ; Simkin et al 2014 ). The overall quality of these six studies were judged based on the inclusion of comparison or control groups in which subjects received an experimental manipulation that was not z-score or LNFB training.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, traditional cognitive rehabilitation typically applies offline behavioral reward (e.g., money). Growing evidence supports the idea that the ultimate biofeedback is to reward with sensory pleasure (e.g., enhanced visual clarity) in real-time to neural circuits that are associated with a desired performance, such as excellent memory ( YuLeung To et al, 2016 ) and attention ( deBettencourt et al, 2015 , 2019 ). Using functional neuroimaging, brain regions that have been consistently implicated in neurofeedback or real-time self-modulation include the anterior insula (cognitive control, self-awareness), and the basal ganglia (sensory motor integration, implicit learning), independent of the targeted region-of-interest ( Emmert et al, 2016 ).…”
Section: Significance Of Working Memory and Improvementmentioning
confidence: 99%